Pelatihan Pembuatan Produk Instan Berbasis Fermentasi Ikan di UMKM Barokah Palembang-Sumatera Selatan: Training of Making Instant Product from Fish Fermented in UMKM Barokah Palembang-South Sumatera - Rinto, Rinto; Herpandi, Herpandi; Widiastuti, Indah; Sudirman, Sabri; Indasari, Dwi; Yunindyawati, Yunindyawati (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
The COVID-19 pandemic, which has spread worldwide since the beginning of 2020, has also impacted the development of the UMKM in Palembang. On the other hand, the Department of Fisheries Product Technology, Faculty of Agricultural, University of Sriwijaya, constantly conducts research based on local resources that have produced patents. One of the resulting patents is for instant bekasam with registration number P00202110332. The community activity program that introduces the technology for making instant products from fermented fish begins with preparations including preparation of supporting facilities and product manufacture. The training on making instant products was attended by more than 30 target audiences who are members of the fish processing and marketing business group in the Keramasan Village, Kertapati District, Palembang. The implementation of activities has been published in print and online media, including via: https://beritapagi.co.id/2022/09/18/unsri-gelar-pelatihan-pembuatan-produk-instan-berbasis-fermentasi-ikan.html